Inventario de la Infraestructura Hidráulica en la Comisión de Usuarios del Subsector Hidráulico Nievería, Lurigancho-Chosica. Lima. 2023 - Zavaleta Horna, Katherin Leticia (2023)
The general objective was to prepare the Inventory of Hydraulic Infrastructure of the Users Commission of the Nievería Hydraulic Subsector, Lurigancho-Chosica. Lime. 2023. For this, the process established in the Regulation of Hydraulic Infrastructure Operators was used, which consisted of the detailed compilation of the characteristics of the hydraulic works and their situational status, information that was processed and entered in the formats established in said regulation. , as well as in the elaboration of the diagram and plan of the hydraulic system. To this is added the systematization of the inventory, through the ArcGis software and the Google Earth geographic browser. The result showed that almost 50 % of the main channel has not yet been lined, the percentage being even lower in the case of lateral channels, added to this, 45,96 % of the lined sections are in poor condition. Likewise, it was evidenced that there is no adequate control and measurement system for water resources. Therefore, it was concluded that the hydraulic system is deficient.